PELATIHAN PEMBUATAN RANSUM AYAM KAMPUNG MENGGUNAKAN AMPAS TAHU DI KELURAHAN SASA TERNATE - Sulasmi; Virlawanti L Baguna (Bajang Institute, 2021)
The maintenance of kampong chickens is still traditional and the lack of understanding of feed management makes chicken productivity less than optimal. Therefore, it is necessary to educate the public about the use of cheap and easily available feed ingredients to support livestock productivity. There are several activities in this Kubermas PKM including socialization and training on making ration chicken rations to the community in Sasa Village which also involves all Kubermas participants. PKM activities are carried out from August to September 2021. The stages of PKM implementation are survey, socialization, training and evaluation. The results showed that there was an increase in knowledge and skills after the PKM Kubermas activity was held in the form of socialization and training on the use of tofu dregs as fodder for kampong chickens in Sasa Village. It is hoped that the people in Sasa Village can understand and practice the material about making rations by utilizing tofu dregs.